2018
DOI: 10.3389/fimmu.2018.00919
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Cyclic AMP Production by the Bordetella pertussis and Bacillus anthracis Adenylate Cyclase Toxins Differentially Affects the Immune Synapse in T Lymphocytes

Abstract: A central feature of the immune synapse (IS) is the tight compartmentalization of membrane receptors and signaling mediators that is functional for its ability to coordinate T cell activation. Second messengers centrally implicated in this process, such as Ca2+ and diacyl glycerol, also undergo compartmentalization at the IS. Current evidence suggests a more complex scenario for cyclic AMP (cAMP), which acts both as positive and as negative regulator of T-cell antigen receptor (TCR) signaling and which, as suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
(88 reference statements)
0
15
0
Order By: Relevance
“…In contrast, ET-triggered cAMP signaling partially inhibited Syk and Vav phosphorylation and had no significant effect on Pyk2 phosphorylation (Figure 2). Indeed, CyaA toxin action instantly leads to the formation of a cAMP pool in the submembranous region of the cytoplasm, which may directly modulate the signaling cascades in the local/specific target region on the cytosolic side of the membrane [50,51]. Further indirect evidence is provided by microscopy experiments where Syk [8], Pyk2 [10], and Vav [13,14] have been shown to be recruited/accumulated in the submembranous region at sites of active uptake of opsonized particles, which is the cytoplasmic subdomain where membrane proximal CyaA-mediated cAMP accumulation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ET-triggered cAMP signaling partially inhibited Syk and Vav phosphorylation and had no significant effect on Pyk2 phosphorylation (Figure 2). Indeed, CyaA toxin action instantly leads to the formation of a cAMP pool in the submembranous region of the cytoplasm, which may directly modulate the signaling cascades in the local/specific target region on the cytosolic side of the membrane [50,51]. Further indirect evidence is provided by microscopy experiments where Syk [8], Pyk2 [10], and Vav [13,14] have been shown to be recruited/accumulated in the submembranous region at sites of active uptake of opsonized particles, which is the cytoplasmic subdomain where membrane proximal CyaA-mediated cAMP accumulation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that microdomains of cAMP have pronounced effects on various signaling processes and major physiological functions in a wide variety of cells [69]. For CyaA, this has been particularly well characterized in T cells where the toxin was shown to efficiently disrupt the immunological synapse and redistribute a number of essential players in the T-cell activation cascade [70,71]. Remarkably, these effects are not elicited by another bacterial toxin, the anthrax edema factor that produces similar cytosolic levels of cAMP but originating from a perinuclear localization-where the toxin is released from late endosomes [71].…”
Section: Plos Onementioning
confidence: 99%
“…For CyaA, this has been particularly well characterized in T cells where the toxin was shown to efficiently disrupt the immunological synapse and redistribute a number of essential players in the T-cell activation cascade [70,71]. Remarkably, these effects are not elicited by another bacterial toxin, the anthrax edema factor that produces similar cytosolic levels of cAMP but originating from a perinuclear localization-where the toxin is released from late endosomes [71]. Hasan et al recently reported similar findings on human monocytes [72].…”
Section: Plos Onementioning
confidence: 99%
“…It is well known that 357 microdomains of cAMP have pronounced effects on various signaling processes and major 358 physiological functions in a wide variety of cells [64]. For CyaA, this has been particularly well 359 characterized in T cells where the toxin was shown to efficiently disrupt the immunological 360 synapse and redistribute a number of essential players in the T-cell activation cascade [65,66]. 361 Remarkably, these effects are not elicited by another bacterial toxin, the anthrax edema factor 362 that produces similar cytosolic levels of cAMP but originating from a perinuclear localization -363 where the toxin is released from late endosomes [66].…”
mentioning
confidence: 99%
“…For CyaA, this has been particularly well 359 characterized in T cells where the toxin was shown to efficiently disrupt the immunological 360 synapse and redistribute a number of essential players in the T-cell activation cascade [65,66]. 361 Remarkably, these effects are not elicited by another bacterial toxin, the anthrax edema factor 362 that produces similar cytosolic levels of cAMP but originating from a perinuclear localization -363 where the toxin is released from late endosomes [66]. Hasan et al recently reported similar 364 findings on human monocytes [67].…”
mentioning
confidence: 99%